Financial crises and business cycle implications for Islamic and Non-Islamic bank lending in Indonesia - Samar Issa (Journal of Risk and Financial Management, 2022)
This paper addresses if and how excess debt can be considered as an early warning signal for banks and takes an additional dimension by comparing the excess leverage between Islamic and conventional banks in Indonesia before, during, and after the Global Financial Crisis (GFC). To do so, this research develops an empirical model of banks' capital structure and optimal and excess debt, and it conducts an empirical analysis on the overleveraging of eleven conventional and Islamic banks in Indonesia. Results show that all banks became vulnerable to the GFC in 2007-2009 while credit build-up, i.e., overleveraging, started in 2005. However, for most of the banks in the sample, Islamic banks performed better and leveraged less prior to the GFC, which made them more resilient to the crisis.
Keywords: 650; banking instability; banking sector; credit flows; early warning signals; excess debt; financial crisis; Islamic banking